Intrinsic and extrinsic factors associated with range of motion (ROM) with an emphasis on a novel genetic factor - Brown, James Craig (MRC/UCT RU for Exercise and Sport Medicine, 2014)
Introduction: Although there are numerous health benefits associated with participating in regular physical activity, there is also an increased risk of sustaining injuries, in particular musculoskeletal soft tissue injuries. Both an increased and decreased joint range of motion (ROM) has been reported as one of the intrinsic risk factors for these injuries. Similarly to injury, the ROM trait has also been associated with various extrinsic and intrinsic factors. Extrinsic factors that are associated with ROM include level and type of sports participation and temperature. Intrinsic factors include age, gender, limb dominance, weight/BMI, height, prior injury, flexibility training, ethnicity and genotype. It has been reported that ROM is a largely (47-70%) heritable trait in both pathological and apparently healthy populations. Mutations within the COL5A1 gene cause classic Ehlers-Danlos Syndrome (EDS) which present with, among other clinical signs, generalised joint hypermobility. Furthermore, a COL5A1 gene sequence variant, the BstUI Restriction Fragment Length Polymorphism (RFLP), has previously been shown to be associated with ROM measurements in a cohort containing individuals with a history of Achilles tendon injuries. Objectives: The aim of this study was, therefore, to investigate the association between the COL5A1 BstUI (C/T) and DpnII (C/T) RFLPs, as well as non-genetic intrinsic and extrinsic factors, and ROM measurements in an apparently healthy and physically active population. 15 Methods: The sit and reach (SR), passive straight leg raise (SLR) and shoulder internal (ShIR) and external rotation (ShER) assessments were performed on 325 (204 males, 121 females) white, apparently healthy and physically active subjects. Subjects were genotyped for the BstUI (SNP rs12722) and DpnII (SNP rs13946) RFLPs within the 3-untranslated region (UTR) of the COL5A1 gene. Level and type of sport participation, age, gender, limb dominance, height, weight, BMI, waist circumference, prior injury and flexibility training were also recorded to investigate possible associations with ROM. Results: There was a significant interaction between age and COL5A1 BstUI genotype with SR ROM. Subjects with a CC genotype were 'protected' against the commonly reported age-related decline in SR ROM. This divergence in response to aging resulted in a significant difference in the mean SR ROM between the BstUI RFLP genotype groups of the 'old' ('¥35 years) (TT=225 Â± 96 mm, TC=245 Â± 100 mm, CC=321 Â± 108 mm, N=96, p=0.017), but not the 'young' (<35 years) (N=197, p=0.626) subjects. While the DpnII RFLP displayed a similar pattern of divergence in SR ROM with aging, this interaction was not significant. Nevertheless, the SR means were significantly different between DpnII genotypes in the 'old' group when the TT and TC genotypes (T allele) were combined and compared against the CC genotype (T allele=244 Â± 98 mm, CC genotype=332 Â± 15 mm, N=93, p=0.032). Furthermore, flexibility training (stretching) was associated with increased ROM only in the BstUI TT genotype, suggesting a genotype-specific response. Of all the intrinsic and extrinsic factors 16 investigated in this cohort, only gender and genotype (either BstUI or DpnII RFLPs) were shown to contribute to SR ROM variance through multivariate analysis. Some inconsistent associations with intrinsic and extrinsic factors were observed with the SLR and shoulder ROM assessments, although small sample size and poor reliability of these measures made the results difficult to interpret with confidence. Conclusion: The significant interaction of COL5A1 BstUI RFLP genotype with age explains the differences in SR ROM measurements observed in older, but not younger, apparently healthy and physically active individuals. A similar, non-significant pattern in the DpnII RFLP resulted in significantly different SR ROM for the T allele in comparison to the CC genotype. Besides genotype, gender also an contributed significantly to SR ROM variance in the 'old' cohort. Genetic sequence variants, in conjunction with commonly listed non-genetic intrinsic and extrinsic factors, need to be considered in order to understand the observed variance in ROM in apparently healthy and physically active populations. Keywords: COL5A1 genotype, range of motion (ROM), apparently healthy and physically active population, intrinsic and extrinsic factors, age, flexibility training.